Recovery Diary Survey: Exploring Caretaker Practices and Cat Behavior after Trap-Neuter-Return (TNR) - Kowalski, Amanda (Tufts Archival Research Center, 2019)
Trap-Neuter-Return (TNR) is a widely accepted practice for humanely controlling free-roaming cat populations. While there are thousands of organizations and individuals that support and regularly use TNR, there is virtually no published data on the practices of free-roaming cat caretakers that would inform a standardized set of guidelines. The study presented in this paper is Part One of a two part research project, The Recovery Diary Survey, which aims to gather data on the practices of free-roaming cat caretakers and trappers, specifically investigating post-operative practices and the behaviors of the cats during their recovery in the United States.; Thesis submitted for the MS in Animals and Public Policy degree.